The influence of Sanskrit aesthetic on the language and structure of Raja Rao's " The Serpent and the Rope” - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education; Vol 7 No 4 (2022): Journal of Advanced Research in English & Education, 2022)
Raja Rao's magnum opus, "The Serpent and the Rope" (1960), stands as a seminal work in post-colonial literature, notable not only for its thematic engagement with the intricate encounter between Eastern and Western consciousness but for its profound linguistic and structural innovations. This article argues that the novel's distinctive aesthetic is deeply rooted in the principles of Sanskrit literature and philosophy, a deliberate choice by Rao to articulate a uniquely Indian worldview. We will explore how the novel's narrative voice, with its contemplative and digressive nature, mirrors the Socratic method of the Upanishads, where knowledge is sought through dialogue and dialectical inquiry rather than linear exposition. The article will further analyze the influence of Sanskrit poetics, particularly the concepts of rasa (aesthetic sentiment) and dhvani (suggested meaning), on the novel's emotional and symbolic layers. By examining the cyclical and non-linear structure of the narrative, the article will demonstrate its resonance with the cyclical understanding of time in Hindu philosophy, contrasting sharply with the linear progression of the Western novel. Through an examination of specific passages, we will show how Rao infuses English with a Sanskrit cadence, utilizing a syntax that echoes the compound structures and philosophical weight of Sanskrit prose. Ultimately, this study contends that "The Serpent and the Rope" is more than a novel about India; it is a novel structured as India, a text whose form and language are themselves a manifestation of a Sanskrit metaphysical worldview.